2020
DOI: 10.1038/s41598-020-70984-1
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous proline induces regulation in 2-acetyl-1-pyrroline (2-AP) biosynthesis and quality characters in fragrant rice (Oryza sativa L.)

Abstract: Proline is one of the precursors of the biosynthesis of 2-acetyl-1-pyrroline (2-AP) which is the key and characteristic volatile component of fragrant rice aroma. In order to study the effects of exogenous proline on 2-AP biosynthesis and other grain quality attributes in fragrant rice, two indica fragrant rice cultivars, "Meixiangzhan-2" and "Xiangyaxiangzhan", and one japonica fragrant rice, "Yunjingyou", were used in present study. At initial heading stage, proline solutions at 0 (CK), 0.10 (Pro1), 0.20 (Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Proline was recognized as the precursor for 2AP biosynthesis [18]. Although PDH plays a crucial part in proline degradation [19,20], its activity presented an opposite trend with increased proline contents. In contradiction to earlier findings [20], the increase in proline contents reduced the activity of PDH and the transcript level of ProDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proline was recognized as the precursor for 2AP biosynthesis [18]. Although PDH plays a crucial part in proline degradation [19,20], its activity presented an opposite trend with increased proline contents. In contradiction to earlier findings [20], the increase in proline contents reduced the activity of PDH and the transcript level of ProDH.…”
Section: Discussionmentioning
confidence: 99%
“…Although PDH plays a crucial part in proline degradation [19,20], its activity presented an opposite trend with increased proline contents. In contradiction to earlier findings [20], the increase in proline contents reduced the activity of PDH and the transcript level of ProDH. The decline in PDH activity could be attributed to transcript reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, lower levels of leaf proline contents at MS represent the higher aroma volatile (i.e., 2‐AP) contents in rice grains due to its conversion to 2‐AP via the above‐mentioned phenomena. Recently, Luo et al (2020) reported that exogenous proline application substantially improved the grain 2‐AP contents by up‐regulating the endogenous P5C and △1‐pyrroline contents, proline dehydrogenase (ProDH) activity and transcription level of PRODH gene. Yoshihashi et al (2002) also found increased 2AP and/or aroma in seedlings and developing callus of fragrant rice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the synthesis of 2AP might also be affected by the expression of the GAPDH (Glyceraldehyde-3-phosphate dehydrogenase), TPI (Triosephosphate isomerase), P5CR (Pyrroline-5-carboxylate reductase), PRODH (Proline dehydrogenase), P5CS (Δ 1 -pyrroline-5-carboxylate synthetase), and OAT (Ornithine aminotransferase). The low expression level of GAPDH and the high expression levels of TPI , P5CR , PRODH , and P5CS in aromatic rice were found to be related to the synthesis of 2AP [ 9 , 25 , 26 , 27 ]. Similar expression patterns were also observed for GAPDH and TPI in aromatic soybeans, but the expression levels of PRODH , P5CS and OAT did not differ between aromatic and non-aromatic soybeans [ 5 ].…”
Section: Introductionmentioning
confidence: 99%